Fatores que podem contribuir para a ocorrência de acidentes de trabalho pelo uso de agrotóxicos entre os agricultores familiares no Assentamento Guapirama em Campo Novo do Parecis-MT - Szniowski, Adelice Minetto (2009)
The central issue of this investigation was to identify the factors which may contribute to the occurrence of work accidents in the use of pesticides. In order to do so, a qualitative form of approach was adopted, involving action research as well as bibliographic research related to the pesticide topics, including aspects such as the origin of these products, their introduction in Brazil, their risks to the human health and the protection measures. Bibliography concerning the area of ergonomics was also used as a base for the ergonomic analysis of work (AET). The use of this methodology made possible to answer the questions posed when in the field research with three families of agricultural workers legally settled in the Assentamento Guapirama, located in the municipality of Campo Novo do Parecis-MT, where the process of soybean cultivation was followed due to its intense use of pesticides. The data resulted from the in loco observation made evident the workers total lack of prepare when dealing with these products. This is a result of the absence of orientation for its correct manipulation, since the institutions that have contact with these agricultural workers omit the hazards or only mention the benefits, which contributes to the lack of information about the risks they are exposed to in their work, so they repeat the behavior adopted in the past. Facing the situation observed, it was verified that the facts which lead to the possible pesticide intoxication go beyond the behavior of the agricultural labourers in their work activity.